Absenteeism study in a steel industry of São José dos Campos, SP, Brazil - Isa Azevedo de Almeida Marote; Dagmar de Paula Queluz (Brazilian Journal of Oral Sciences, 2017)
Aim: To identify the factors involved in absenteeism in a steel industry in the city of São Jose dos Campos, São Paulo, Brazil. Methods: A cross-sectional study was carried out after obtaining permission from Institutional Ethics Committee in a steel industry. Worker's detailed information regarding absenteeism was obtained from the Health Department files, from January 2005 to December 2008. Specifical data were: sex, function, certificate type (medical or dental), the working sector, according to the Large Groups (LG) of Brazilian Classification of Occupations - 2002, working periods, duration of absenteeism (lost days), the main causes of absenteeism (International Classification of Diseases ICD-10). Results: A total of 570 workers were recorded. The majority of workers were males (97%), with medical certificate (97%), LG-7 workers in the production of industrial goods and services (62.09%), and operators of industrial machinery (68.3%) and the working period was Shift 4 - Monday to Friday from 8 am to 12 am and 1 pm to 5 pm (44.43 %). The total duration of absenteeism was 3,187 days, the main causes of diseases being problemas in the musculoskeletal system and connective tissue (18.48%), respiratory diseases (17.11%), injuries, poisoning and other external causes (11.24%), and diseases of the digestive tract (11.24%). Conclusions: It was concluded that there was under-reporting of absenteeism due to dental causes (41 events) during the study period. More studies in this field are required.